De-twinning and Texture Change in an Extruded AM30 Magnesium Alloy during Compression along Normal Direction. Issue 3 (March 2015) - Sarker, D.; Friedman, J.; Chen, D.L.
Abstract : Twinning and de-twinning are the salient deformation mechanisms in hexagonal close-packed (hcp) metals. The aim of this study was to examine and quantify the de-twinning process involving a reversible motion of twin boundaries in an extruded AM30 magnesium alloy after re-compression along the normal direction (ND) of pre-compressed samples along the extrusion direction (ED). {10 1 ¯ 2} extension twins were first introduced at a compressive strain of 3.7% along the ED. The subsequent compressive deformation along the ND induced a gradual shrinkage of twins with increasing cumulative true strain, and the complete de-twinning occurred at a strain of ∼7.7%. The twin width decreased linearly with increasing true strain. Texture measurements verified the rotation of c -axes of hcp unit cells towards the anti-compression direction due to {10 1 ¯ 2} extension twinning after compression along the ED, and a gradual return of c -axes to the initial orientation due to twin shrinking or de-twinning during the following compression along the ND. The {10 1 ¯ 2} twinning corresponded to the formation of new texture components C{ 1 ¯ 2 1 ¯ 0}<0001> and D{01 1 ¯ 0}<0001> and a decrease in the initial texture components A{0001}<2 1 ¯ 1 ¯ 0> and B{0001}<10 1 ¯ 0>, while the twin shrinking or de-twinning was characterized by a gradual vanishing of components C{ 1 ¯ 2 1 ¯ 0}<0001> and D{01 1 ¯ 0}<0001> and an increase in the components A{0001}<2 1 ¯ 1 ¯ 0> and B{0001}<10 1 ¯ 0>.